Whistleblowing: Legal and moral quandaries in public procurement process - Ahmad, Rusniah; Khalil, Samihah (2011)
﻿Whistle blowing occurs in any organization and that includes in the public sector.This work will discuss whistle blowing woes in public procurement processes which inevitably must be addressed by employers or those in authority.Within an organisation whistle blowing is an act of alerting on the scandal, malpractice or corruption where wrongdoings maybe of illegal or unethical activities.They could call about or give tip-offs on thefts, frauds, bullying, harassment, discrimination, environmental hazards, breaches of policy and other unethical acts or misconduct.Being basically a form of disclosure, a person will become a whistle blower when he/she initially raises serious concerns about the incident of wrongdoing and the risks of the wrongful activities or wrongdoings within an organisation. Respectively, this work will address three issues in whistle blowing -morality, legality and ethics. These are fundamental issues which must not be ignored and that the laws and regulations must be clarified in order to ensure that procurement exercises are conducted in the utmost respect and fairness.Whistle blowing could be used as a tool to achieve this ideal and that consideration for such possibilities must not be dismissed in total disregard of its potentialities and use. The need to legally protect those who blow the whistle will also be discussed.